2013
DOI: 10.1016/j.celrep.2013.10.050
|View full text |Cite
|
Sign up to set email alerts
|

Exosome Secretion Is Enhanced by Invadopodia and Drives Invasive Behavior

Abstract: Summary Unconventional secretion of exosome vesicles from multivesicular endosomes (MVE) occurs across a broad set of systems and is reported to be upregulated in cancer where it promotes aggressive behavior. However, regulatory control of exosome secretion is poorly understood. Using cancer cells, we identified specialized invasive actin structures called invadopodia as specific and critical docking and secretion sites for CD63- and Rab27a-positive MVE. Thus, inhibition of invadopodia formation greatly reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
472
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 471 publications
(494 citation statements)
references
References 24 publications
21
472
0
1
Order By: Relevance
“…H-I, Growth factor starved WT MCF10A cells were seeded to plastic or fibronectin-coated plates and treated with the indicated doses of AREG. After 7 days, proliferation was assessed by crystal violet staining, H. Lysates were prepared for immunoblot analysis after 3 days, I. J, The number of microvesicles or exosomes harvested from starvation media conditioned We previously reported that exogenous expression of PIK3CA H1047R promotes exosome secretion in head and neck cancer cells (30). To test this in knock-in PIK3CA mutant MECs, we purified exosomes and larger shed microvesicles from conditioned media.…”
Section: Figmentioning
confidence: 99%
“…H-I, Growth factor starved WT MCF10A cells were seeded to plastic or fibronectin-coated plates and treated with the indicated doses of AREG. After 7 days, proliferation was assessed by crystal violet staining, H. Lysates were prepared for immunoblot analysis after 3 days, I. J, The number of microvesicles or exosomes harvested from starvation media conditioned We previously reported that exogenous expression of PIK3CA H1047R promotes exosome secretion in head and neck cancer cells (30). To test this in knock-in PIK3CA mutant MECs, we purified exosomes and larger shed microvesicles from conditioned media.…”
Section: Figmentioning
confidence: 99%
“…1A and B), some of the findings in the IS model might be usefully applied to other systems. Recent studies suggest that both structures are similar and both are exosome-targeting sites that might be determined by the same fundamental molecular combination of actin, microtubules and integrins 27,28 ; other studies years ago highlighted significant parallels between the mechanisms that regulate the formation of IS and of podosomes, a invadopodium-like structure. 29 Similar reasoning led Griffiths et al to state that the IS bears a resemblance to other structures in which an area of the PM becomes a focal zone for endo-and exocytosis, for example during cilia formation and cytokinesis.…”
Section: Static Dynamic and Polarized Models For Vesicle Traffickingmentioning
confidence: 99%
“…Exosomes are recruited at the plasma membrane of tumor cell invadopodia, the tumor cell structures which release metalloproteinases for extracellular matrix degradation (Hoshino et al 2013. Transfer of exosomes extracted from tumor provided with invadopodia induces invadopodia formation in non-invading cells (Hoshino et al 2013). Moreover, the ability of the cancer-released exosomes to influence the stromal 'premetastatic' niche in the potential target metastatic organs has recently been hypothesized.…”
Section: Exosomes and Tumor Microenvironment In Acc Progressionmentioning
confidence: 99%
“…Exosomes released by tumor cells and environmental stroma appear critical for supporting processes involved in metastasis, such as angiogenesis, tumor invasion, extracellular matrix digestion, cell motility and immunomodulatory escape activity of the tumor (Milane et al 2015, Suchorska & Lach 2016. Exosomes are recruited at the plasma membrane of tumor cell invadopodia, the tumor cell structures which release metalloproteinases for extracellular matrix degradation (Hoshino et al 2013. Transfer of exosomes extracted from tumor provided with invadopodia induces invadopodia formation in non-invading cells (Hoshino et al 2013).…”
Section: Exosomes and Tumor Microenvironment In Acc Progressionmentioning
confidence: 99%